2006
DOI: 10.1002/hyp.6200
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate change and its effects on river runoff in the Tarim Basin, China

Abstract: Abstract:The hydrological response to climate change in the Tarim River Basin was investigated by analysing the hydrological, temperature and precipitation data of the past 50 years. The long-term trend of the hydrological time-series, including air temperature, precipitation, and streamflow, was examined by using both parametric and non-parametric techniques and the plausible association between streamflow and climate change by the method of grey correlation analysis. The results show that the study area beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
164
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(184 citation statements)
references
References 11 publications
16
164
3
1
Order By: Relevance
“…Therefore, there are conceivably close relationships between runoff and a set of regional climate factors, especially temperature and precipitation. This perception is supported by the results of some previous studies for the headwaters of the Tarim River Basin (Xu et al, 2004;Jiang et al, 2005;Chen et al, 2006;Zhang et al, 2008;Xu et al, 2009b). From the physical mechanism, the temperature mainly influences the runoff by glacier melt and snowmelt while Notes: AR -annual runoff, AP -annual precipitation, PFS -precipitation in flood season, AAT -average annual temperature, ATSP -average temperature in spring, ATSU -average temperature in summer, ATA -average temperature in autumn, and ATW -average temperature in winter.…”
Section: Ranking Of Climate Factors In Order Of Importancesupporting
confidence: 80%
“…Therefore, there are conceivably close relationships between runoff and a set of regional climate factors, especially temperature and precipitation. This perception is supported by the results of some previous studies for the headwaters of the Tarim River Basin (Xu et al, 2004;Jiang et al, 2005;Chen et al, 2006;Zhang et al, 2008;Xu et al, 2009b). From the physical mechanism, the temperature mainly influences the runoff by glacier melt and snowmelt while Notes: AR -annual runoff, AP -annual precipitation, PFS -precipitation in flood season, AAT -average annual temperature, ATSP -average temperature in spring, ATSU -average temperature in summer, ATA -average temperature in autumn, and ATW -average temperature in winter.…”
Section: Ranking Of Climate Factors In Order Of Importancesupporting
confidence: 80%
“…The simulation results of Singh and Bengtsson (2004) showed that increasing temperatures caused decreases in streamflow in winter, summer, and autumn; however, streamflow increased in spring in western Himalayan rivers. Chen et al (2006) reported significant and subtle increasing trends and slight decreasing trends in streamflow at different headwaters of the Tarim River when temperature and precipitation increased.…”
Section: 'Revisiting' Hydrological History Using Model Simulationmentioning
confidence: 98%
“…An inflection point (in 1986) was identified through visual observation, and this coincides with the Tarim River Basin in north-west China (Chen et al, 2006). The annual temperature of two meteorological stations in Yunnan Province (Tengchong Station 180 km away from Longyang Station and Kunming Station about 580 km away from Longyang Station) were tested to show the trend in temperature change in Baoshan.…”
Section: Changes In Temperature Rainfall and Streamflowmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, increasing annual mean runoff was observed in the East River and the Yangtze River basins, South China (Zhang et al 2015;Zhang et al 2006). In Northwest China, runoff also increased during the past 50 years, with a step-like change in precipitation at approximately 1986 (Chen et al 2006). In contrast, in the Yellow River basin, runoff has been decreasing in recent decades (Zhang et al 2009).…”
mentioning
confidence: 99%